Advances in Aerospace Guidance, Navigation and Control Selected Papers of the 1st CEAS Specialist Conference on Guidance, Navigation and Control - Holzapfel, Florian; Theil, Stephan (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Over the last few decades, both the aeronautics and space disciplines have greatly influenced advances in controls, sensors, data fusion and navigation. Many of those achievements that made the word "aerospace" synonymous with "high-tech" were enabled by innovations in guidance, navigation and control.   Europe has seen a strong trans-national consolidation process in aerospace over the last few decades. Most of the visible products, like commercial aircraft, fighters, helicopters, satellites, launchers or missiles, are not made by a single country - they are the fruits of cooperation. No European country by itself hosts a specialized guidance, navigation and controls community large enough to cover the whole spectrum of disciplines. However, on a European scale, mutual exchange of ideas, concepts and solutions is enriching for all. The 1st CEAS Specialist Conference on Guidance, Navigation and Control is an attempt to bring this community together.   This book is a selection of papers presented at the conference. All submitted papers have gone through a formal review process in compliance with good journal practices. The best papers have been recommended by the reviewers to be published in this book.